‘Ring the Bells’: Sound and Silence in Garth Nix’s Old Kingdom - Sean Williams (Humanities)
Australian author Garth Nix has set six critically acclaimed and internationally bestselling novels and several shorter works in and around the fictional world of the Old Kingdom, beginning with Sabriel (1995) and continuing most recently with Terciel & Elinor (2021). This loose series of texts, with its bellringing protagonists, is the prime contributor to his reputation as an author of high fantasy fiction, although he is also marketed as and known for writing science fiction and other related subgenres. Most notably, his work prominently features elements of the Gothic. This aspect of his work and the ways in which it creates tension within the “high” fantasy genre becomes increasingly apparent when examined through the lens of sound—a critical method that has potential for charting the entanglements of this genre with other popular genres of fiction.